PREVALENCE OF OBESITY AND RELATED HEALTH RISK FACTORS IN URBAN ADULTS: A CLINICAL SURVEY: Pharmaceutical Science-Pharmacology - SWATI SHARMA; SANDEEP KUMAR SINGH (International Journal of Life Science and Pharma Research, 2022)
Obesity is touching its peak globally; with a count of approximately 1 billion overweight adults and at least 300 million clinically obese and becoming a major risk for serious diet- related chronic diseases. This study estimates the pattern and prevalence of obesity in different sections of adults in a particular population. The data set of a population-based case-control study was analyzed. Data were collected from a representative sample of 220 adults (aged 15-60 years, 107 females and rest males) chosen randomly from college campus, and various areas of Lucknow. The survey followed an interactive sessions with these peoples through questionnaire in which main emphasis was laid on the Body Mass Index (BMI), lifestyles, food habits, related health problems of the peoples along with preventive measures taken by them to avoid obesity. Then the data were analyzed using pie charts, line charts, column charts and bar diagrams to show the final percentage. With few exceptions, most of the obese patients were found to habitual of eating unhealthy food, lacking exercise and BMI between 25-29.9. Compared with peoples of age group below 30 yrs, peoples with age group in the range of 30-60 were large in percentage in having chronic diseases like diabetes; heart problems etc., but there were many cases that were having high blood pressure and asthma type problems in the age of 18-30. These results suggest that there is no optimal age for the occurrence of obesity and related problems in adult life and that excessive weight gain may begin at any time. The risk factors of obesity and health problems are multifactorial and variable in percentage among populations.